Penerapan Stategi Indeks Card Match untuk Meningkatkan Minat Belajar Siswa pada Materi Operasi Hitung Bilangan Bulat - Daulay, Irma Sari; Nasution, Winda Wahyuni; Nasution, Windi Wahyuni; Nasution, Salsabilah Rizki Mintana; Syaputra, Rizzy Riady (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to increase students' interest in learning Mathematics, especially the material of arithmetic operations of integers, through the application of the Index Card Match learning strategy. The study was conducted at SD Negeri 0209 Bahal Batu with subjects of grade VI students in the even semester of the 2024/2025 academic year. The type of research used was Classroom Action Research (CAR) which was carried out in two cycles. Each cycle consisted of planning, action, observation, and reflection stages. Data were collected through observation, learning interest questionnaires, learning outcome tests, and documentation. The results of the study showed a significant increase in students' interest in learning after the implementation of the Index Card Match strategy. This was seen from the average increase in students' interest in learning from 62.4 in cycle I to 83.1 in cycle II so that students had achieved or exceeded the Minimum Competency (KKM). Based on the results of qualitative and quantitative analysis, the Index Card Match strategy proved effective in creating a pleasant learning atmosphere and increasing students' interest in learning mathematics.